Analisis Rancangan Tata Ruang Toko dalam Bisnis Retail Indomaret Plus Padasuka Ciomas Bogor - Annisa, Putri Dwi; Fatimah, Malida; Yudistira, Linsang Jallu (Center for Study and Journal Management FTI UMI, 2025)
Resilience in the face of delays in the distribution of humanitarian logistics is a crucial aspect in post-disaster response. This study aims to analyze the factors that affect the resilience of disaster victims in the context of logistics delays using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. This research model adopts three main constructs, namely Sense of Mastery (SoM), Sense of Relatedness (SoR), and Emotional Reactivity (ER), which are assumed to contribute to individual resilience (RES). Data was collected through a questionnaire-based survey of individuals who had experienced delays in the distribution of humanitarian aid. The results of the analysis show that SoM and SoR have a significant positive influence on resilience. In contrast, ER has a negative relationship with RES, which means that the higher a person's level of emotional reactivity, the lower their level of resilience in the face of delays in help. In the initial model, there are several indicators showing low outer loading values so they are excluded from the final model, because they do not contribute significantly to other variables. After refining the model, the reliability results show that the remaining constructs have good validity and reliability values. Strong R-square values for all endogenous variables (SoM = 0.962, SoR = 0.894, ER = 0.981, RES = 0.944) confirm that the model has high predictive ability in explaining resilience in the context of delays in the distribution of human logistics. The results of this study can be the basis for policymakers and stakeholders in developing a more optimal aid distribution system, as well as mitigation strategies that can increase the resilience of disaster victims in facing future logistical challenges